Szkoła wobec problemu wychowania i nauczania = School towards the problem of education and teaching - Szołtysek, Adolf E. (Zielona Góra: Uniwersytet Zielonogórski)
The dissertation takes up the issue of dilemmas of contemporary school in the context of various dangers. It consists of the answers to the following questions: What are the ethical problems of school? What are the moral problems of a family? What traits should characterise a teacher? What mistakes of teachers should be recognised as typical? Is the extra-school education possible?
Keywords: wychowanie; edukacja; szkoła